Evaluation of Serum Calcium Element among Type 2 Diabetes Mellitus Patients at Al-Zawia Medical Centers-Western Libya - Al Basher Ashour; Siddig Bushra Mohamed; Marwa Almabrok; Salih Elmahdi (AlQalam Journal of Medical and Applied Sciences, 2025)
Diabetes mellitus is an endocrinal condition marked by poor carbohydrate metabolism. The objective of this study is to assess the status of serum calcium among type 2 diabetes mellitus patients attending Al-Zawia medical centers, western Libya. This is a descriptive-cross-sectional design study, among One hundred and forty (140) diagnosed type 2 diabetes mellitus patients, both gender (70 males and 70 females) was recruited during the period from December 2024, to April 2025, demographic data were collected by validated structured questionnaire, and analyzed, by medical statistician as frequency and percentage calculation. The frequency of low calcium was found in 52(37.1%) patients, 28 of them females, 24 males and the normal calcium was found in 67(47.85%) of the total diabetes mellitus patients. In the other hand, the frequency of hypercalcemia was seen in 21(15%) of the patients. This study concluded that hypocalcemia 52(37.1%) and hypercalcemia 21(15%) was moderately related to our research study on type-2 diabetes mellitus.